Budesonide and fluticasone propionate differentially affect the airway epithelial barrier. Issue 1 (December 2016) - Heijink, I.; Jonker, M.; de Vries, M.; van Oosterhout, A.; Telenga, E.; ten Hacken, N.; Postma, D.; van den Berge, M.
Abstract Background COPD patients have a higher risk of pneumonia when treated with fluticasone propionate (FP) than with placebo, and a lower risk with budesonide (BUD). We hypothesized that BUD and FP differentially affect the mucosal barrier in response to viral infection and/or cigarette smoke. Methods We assessed protective effects of equivalent concentrations of BUD and FP on cytokine production and barrier function (electrical resistance) in human bronchial epithelial 16HBE cells and primary bronchial epithelial cells (PBECs) upon exposure to viral mimetic poly-(I:C) and/or cigarette smoke extract (CSE) or epidermal growth factor (EGF). Results BUD and FP were equally effective in suppressing poly-(I:C)- and/or CSE-induced IL-8 secretion in 16HBE and PBECs. Poly-(I:C) substantially decreased electrical resistance in 16HBE cells and both BUD and FP fully counteracted this effect. However, FP hardly affected 16HBE barrier dysfunction induced by CSE with/without poly-(I:C), whereas BUD (16 nM) provided full protection, an effect likely mediated by affecting EGFR-downstream target GSK-3β. Similarly, BUD, but not FP, significantly improved CSE-induced barrier dysfunction in PBECs. Finally, BUD, but not FP, exerted a modest but significant protective effect againstStreptococcus Pneumoniae- induced barrier dysfunction, and BUD, but not FP, prevented cellular adhesion and/or internalization of these bacteria induced by poly-(I:C) in 16HBE. Conclusions Collectively, both BUD and FP efficiently control epithelial pro-inflammatory responses and barrier function upon mimicry of viral infection. Of potential clinical relevance, BUD more effectively counteracted CSE-induced barrier dysfunction, reinforcing the epithelial barrier and potentially limiting access of pathogens upon smoking in vivo.